Ethnobotanical survey and scientific validation of liver-healing plants in northeastern Morocco - Bencheikh, Noureddine; Elbouzidi, Amine; Baraich, Abdellah; Bouhrim, Mohamed; Azeroual, Abdelhamid; Addi, Mohamed; Mothana, Ramzi A.; Al-Yousef, Hanan M.; Eto, Bruno; Elachouri, Mostafa (Frontiers in Pharmacology, 2024)
Liver diseases pose a significant global health challenge, primarily stemming from various factors such as excessive alcohol consumption, infections, chemotherapy, and autoimmune disorders. Medicinal plants, with their natural compounds, offer a promising avenue for the development of unique and effective treatments and preventive measures for liver ailments.This study focused on conducting an ethnobotanical survey in remote communities of northeastern Morocco with two primary objectives: (1) compiling a record of herbal remedies used by the local population to address liver diseases, and (2) establishing a correlation between the documented ethnopharmacological uses and supporting scientific evidence through a bibliometric analysis. Using semi-structured questionnaires, we interviewed 189 informants between October 2020 and January 2022 to gather ethnobotanical information. The collected data underwent analysis using four ethnobotanical quantitative indices: use value (UV), familial use value (FUV), informant consensus factor (ICF), and fidelity level (FL). A total of 45 plant species from 26 different families were identified for the treatment of liver ailments. Among these, Cuminum cyminum L. (UV=0.1065) emerged as the most commonly utilized plant species, followed by Allium sativum L. (UV=0.1015), Salvia officinalis L. (UV=0.0761), Asparagus officinalis L.(UV=0.0558), and Ziziphus lotus (L.) Lam. (UV=0.0457). The Apiaceae family had the highest familial use value (FUV = 0.1066), followed by Alliaceae (FUV = 0.1015). Notably, the highest informant consensus factor (ICF) value was associated with liver congestion (ICF=0.83), followed closely by hepatic colic (ICF=0.80). When examining the scientific literature, it was found that 61% of the selected plants had been validated for their pharmacological effects in addressing liver issues. These medicinal herbs could potentially serve as a dependable therapeutic approach for liver conditions. However, it is imperative to conduct further rigorous investigations to confirm their effectiveness in individuals with hepatic impairment. In conclusion, this research can serve as a valuable database for future studies in this field.